Reception Theory and Reading in the Digital Space (Aesthetics of Interactive Digital Reception) - boubaker, rofaida; benstiti, sadia (El Omda in Linguistics and Discourse Analysis, 2022)
Literature and criticism interact with technology through a range of media shaped by the contemporary era. There is no doubt that incorporating modern technologies into both fields opens up new possibilities for renewal and transformation. Accordingly, theories—including reception and reading theory—have moved into new stages of theorization and application, which is what this research ultimately concludes.